Education and Ethnic Communities: Towards an Inclusive Framework - Bachan, K.H. Amitha; G., Swetha; Mohan, Maya (INDIAN EDUCATIONAL REVIEW, 2014)
Inclusive framework to education aims to reorient curriculum to address the learning styles and needs of students coming from diverse backgrounds. The vulnerabilities for the children to take advantage of educational opportunities may be because of their race, social class, ethnicity, religion, gender or ability (Vitllo and Mithaug 1998). The issue becomes graver in the case of marginalised sections. This paper tries to look at the issue of inclusive education in the context of the educational experiences among an ethnic group Kadar in the state of Kerala, South India. The main arguments of this study are based on the experiences from the preparation and distribution of a locally contextualised education material prepared for ‘Kadar’ and other rural children by Western Ghats Hornbill Foundation (WGHF).